"Good Clinical Practice". The European Community guidelines for trials on medicinal products - Spagnolo, Antonio G. (Medicina e Morale, 1991)
The basic idea of producing European Good Clinica! Practice (GCP) guidelines was to set high common standards far the clinical evaluation of medicinal products. This document was begun in 1985 and completed in 1988. The final approval was given in July 1990 and the guidelines will come into operation in July 1991 well before the beginning of the single drug market in 1993. The author widely analyses and schematizes all the five chapters that refer to: 1) the protection of trial subject and consultation of Ethics Committees, 2) the responsibilities of the sponsor, monitor and investigator, 3) data handling, 4) statistics, and 5) quality assurance. An Annex, intended to provide guidance on some of practical aspects, is also taken into consideration. In the footnotes the author explains several specific terms used in the document the way they are defined in the GCP's Glossary. Morever, he makes his own personal comments about some criticai points. emphasizing the connection between ethical requirements and quality assurance.